ANALYSIS OF INTERNAL CONTROL SYSTEM OF RECEIVABLES AT PT. PUTRADUTA BUANASENTOSA INDOARSIP MEDAN - Liza Widya Hasyim; Khairah Fiddarain (RADJA PUBLIKA, 2025)
The level of effectiveness of the accounting information system can be measured based on the level of ease of use of the information system and the accuracy of the information presented in the company environment. The aim of this research is to analyze the level of effectiveness of the accounting information system for controlling receivables using the method of measuring the level of effectiveness using the Dean J. Champion formula. The results of calculating the effectiveness of accounting information system indicators produce a value of 42%, accounting information system components 48%, and accounts receivable control 50%. This shows that the accounting information system at PT. Putraduta Buanasentosa Indoarsip Medan is less effective so there needs to be a better system update and evaluation of receivables control within the company.